2016
DOI: 10.1038/srep24460
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent VEGFR-2 Inhibitors based on Furopyrimidine and Thienopyrimidne Scaffolds as Cancer Targeting Agents

Abstract: Vascular endothelial growth factor receptor-2 (VEGFR-2) plays a crucial role in cancer angiogenesis. In this study, a series of novel furo[2,3-d]pyrimidine and thieno[2,3-d]pyrimidine based-derivatives were designed and synthesized as VEGFR-2 inhibitors, in accordance to the structure activity relationship (SAR) studies of known type II VEGFR-2 inhibitors. The synthesized compounds were evaluated for their ability to in vitro inhibit VEGFR-2 kinase enzyme. Seven compounds (15b, 16c, 16e, 21a, 21b, 21c and 21e)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(104 citation statements)
references
References 60 publications
5
99
0
Order By: Relevance
“…cerebral cavernous malformation)1314 and cancer angiogenesis151617. HUVECs purchased from the Institute of Cell Biology of the Chinese Academy of Sciences (Shanghai, China) were also used in our previous in vitro studies1218.…”
Section: Resultsmentioning
confidence: 99%
“…cerebral cavernous malformation)1314 and cancer angiogenesis151617. HUVECs purchased from the Institute of Cell Biology of the Chinese Academy of Sciences (Shanghai, China) were also used in our previous in vitro studies1218.…”
Section: Resultsmentioning
confidence: 99%
“…The binding of VEGF-A to VEGFR-2 can induce a cascade of signaling pathways, eventually causing cellular proliferation and endothelial cell survival 18,19. Several studies have confirmed that blocking VEGFR-2 was a promising therapy for inhibiting angiogenesis 20,21.…”
Section: Discussionmentioning
confidence: 99%
“…The target compounds 29a–f were evaluated for their ability to in vitro inhibit VEGFR‐2 kinase enzyme. Several compounds demonstrated highly potent dose‐related VEGFR‐2 inhibition with IC 50 values in nanomolar range (Table ) .…”
Section: Tyrosine Kinasesmentioning
confidence: 99%